Unmanned vehicle systems for geomatics : towards robotic mapping - Armenakis, Costas; Patias, Petros (Whittles Publishing, 2019)
This is a systematic and comprehensive approach for the use of small mobile unmanned systems for robotic geomatics research and applications. It presents the state-of-the-art use of low cost unmanned vehicle systems (UVS) with emphasis on the unmanned aerial systems (UAS) for geomatics technologies and practices and contains the most recent developments in methods, systems and innovative applications